Effect of spacing on growth, carbon sequestration, and wood quality of 8-year-old clonal teak plantation for sustainable forest teak management in Java Monsoon Forest, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Rahmawati RB, Widiyatno, Hardiwinoto S, Budiadi, Nugroho WD, Wibowo A, Rodiana D. 2022. Effect of spacing on growth, carbon sequestration, and wood quality of 8-year-old clonal teak plantation for sustainable forest teak management in Java Monsoon Forest. Biodiversitas 23: 4180-4188. Lowland monsoon forest dominated by teak was one of the tropical forest types that can contribute to producing wood production, carbon storage, reduction of emissions, and other ecosystem services. Increasing teak forest productivity could be obtained through teak breeding to get superior teak clones with high diameter growth. Thus, spacing is an important consideration for optimizing the growth, carbon sequestration, and wood properties of teak. However, the study of the growth, carbon sequestration, and wood quality of teak was conducted separately. This research used a selected teak clone aged 8 years with RCBD design with 4 blocks as replications. There were four different spacing as treatments, namely 10 m x 2 m, 8 m x 2 m, 6 m x 2 m, and 3 m x 3 m. The results showed that spacing was a significant effect on DBH, tree height, bole height, carbon sequestration, and volume of teak clones aged 8 years. On the other hand, spacing didn’t significantly affect the physical and mechanical properties of wood. The wood quality test showed that the 6 m x 2 m spacing had high values of bending strength and compressive strength parallel. The highest percentage of heartwood was at a narrow spacing of 6 m x 2 m and did not differ significantly with wide spacing. This indicated that wide spacing was beneficial in terms of teak growth, but wide spacing didn’t significantly affect on wood quality of the teak.